Thiotriazolin effectiveness in complex treatment of patients with post-COVID syndrome - V. I. Kryvenko; M. Yu. Kolesnyk; I. F. Bielenichev; S. V. Pavlov (Zaporožskij Medicinskij Žurnal)
The aim of this work is to evaluate the complex therapeutic effect of Thiotriazolin (anticoagulant, antiplatelet, metabolitotropic, endothelioprotective activity) in patients with post-COVID syndrome in comparison with basic therapy.